The Islanding effect - a special method of percutaneous peritumor ethanol injection for hepatocellular carcinoma: 15-year follow-up outcome. Issue 3 (22nd January 2021) - Meng, Ze-Wu; Cai, Xin-Ran; Lin, Chang-Zhao; Chen, Yan-Ling; Liu, Song
Abstract : Abstract: Percutaneous ethanol injection is a well-known ablation therapy for hepatocellular carcinoma and is well-tolerated, inexpensive, and effective with few adverse events. In this study, another type of ethanol injection was introduced in the present study. Sixty two patients with hepatocellular carcinoma received 133 percutaneous peritumor ethanol injection treatments and the 15-year follow-up outcomes were analyzed through a collected database. The technical efficiency was 89.5% (119/133 treatments) after the first percutaneous peritumor ethanol injection procedure. However, after the second repeated percutaneous peritumor ethanol injection procedure, technical efficiency increased to 98.5% (131/133 treatments). The 1 year, 3 years, 5 years, 10 years, and 15 years rates of tumor recurrence were 12.9%, 50.0%, 59.7%, 74.2%, and 74.2%, respectively. Multivariate analysis demonstrated that diabetes, Child–Pugh class B, and tumor size greater than 2 cm were significantly related to tumor recurrence. The 1 year, 3 years, 5 years, 10 years, and 15 years rates of overall survival were 98.4%, 83.6%, 61.3%, 19.4%, and 0%, respectively. Multivariate analysis demonstrated that Child–Pugh class B, tumor size greater than 2 cm, and multiple tumors were significantly related to overall survival. Compared with other ablation methods (including peritumor ethanol injection), percutaneous peritumor ethanol injection can avoid tumor ruptures, reduce tumor proliferation and metastasis, and is suitable for the treatment of small tumors. In addition, when combined with other treatment methods, percutaneous peritumor ethanol injection can form a tumor metastatic isolation zone in advance and improve the comprehensive treatment effect.